2022
DOI: 10.3389/fgene.2022.781676
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of circRNA-miRNA-mRNA ceRNA Network in Cardiac Hypertrophy

Abstract: Cardiac hypertrophy is an adaptive cardiac response that accommodates the variable hemodynamic demands of the human body during extended periods of preload or afterload increase. In recent years, an increasing number of studies have pointed to a potential connection between myocardial hypertrophy and abnormal expression of non-coding RNAs. Circular RNA (circRNA), as one of the non-coding RNAs, plays an essential role in cardiac hypertrophy. However, few studies have systematically analyzed circRNA-related comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In another study on animal models of myocardial hypertrophy, 3 mRNA, 4 miRNAs, and 4 circRNAs were found to play an important role in myocardial hypertrophy. Bioinformatics methods were used for the study [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study on animal models of myocardial hypertrophy, 3 mRNA, 4 miRNAs, and 4 circRNAs were found to play an important role in myocardial hypertrophy. Bioinformatics methods were used for the study [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies have recently analyzed the ceRNA network in cardiac hypertrophy/cardiac fibrosis/heart failure ( Gu et al, 2020 ; Chen et al, 2022 ; Li et al, 2022 ). Li et al demonstrated distinct pathological features in the three stages of heart failure and constructed a ceRNA regulatory network in cardiac remodeling and dysfunction ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we had more replicates per group (n = 5), and whole transcriptome RNA-seq was used. Chen et al used data from human iPSC-derived cardiomyocytes from public databases ( Aggarwal et al, 2014 ) and established a circRNA-mediated ceRNA regulatory network in cardiac hypertrophy ( Chen et al, 2022 ), which may not be representative of specific physiopathological features during cardiac hypertrophy. Gu et al determined the circRNA expression profile and conducted constructed a ceRNA network in TGF-β1-treated mouse cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the plug-in can calculate the information of each node in the network diagram. According to recent research studies, the top 25% of nodes in the ceRNA network can be selected [26], and only the complete circRNA-miRNA-mRNA axes were retained.…”
Section: Reconstruction Of the Key Circrna-mirna-mrnamentioning
confidence: 99%